Azole resistance survey on clinical Aspergillus fumigatus isolates in Spain. (August 2021) - Escribano, Pilar; Rodríguez-Sánchez, Belén; Díaz-García, Judith; Martín-Gómez, María Teresa; Ibáñez-Martínez, Elisa; Rodríguez-Mayo, María; Peláez, Teresa; García-Gómez de la Pedrosa, Elia; Tejero-García, Rocío; Marimón, José María; Reigadas, Elena; Rezusta, Antonio; et al.
Abstract: Objectives: We aimed to assess the percentage of azole resistance in Aspergillus fumigatus in Spain. Methods: Thirty participating Spanish hospitals stored all morphologically identified A. fumigatus sensu lato clinical isolates—regardless their clinical significance—from 15 February to 14 May 2019. Isolates showing azole resistance according to the EUCAST 9.3.2 methodology were molecularly identified and the cyp51A gene was studied in A. fumigatus sensu stricto isolates. Results: Eight hundred and forty-seven isolates from 725 patients were collected in 29 hospitals ( A. fumigatus sensu stricto ( n = 828) and cryptic species ( n = 19)). Isolates were mostly from the lower respiratory tract (94.0%; 797/847). Only cryptic species were amphotericin B resistant. Sixty-three (7.4%) out of the 847 isolates were resistant to ≥1 azole(s). Azole resistance was higher in cryptic species than in A. fumigatus sensu stricto (95%, 18/19 vs. 5.5%, 45/828); isavuconazole was associated to the lowest number of non-wild type isolates. The dominant mechanism of resistance was the presence of TR34 -L98H substitutions ( n = 24 out of 63). Out of the 725 patients, 48 (6.6%) carried either cryptic species ( n = 14) or A. fumigatus sensu stricto ( n = 34; 4.7%) resistant isolates. Aspergillus fumigatus sensu stricto harbouring either the TR34 -L98H ( n = 19) or TR46 /Y121F/T289A ( n = 1) mutations were detected in patients in hospitals located at 7/24 studied cities. Discussion: Of the patients, 6.6% carry azole-resistant A. fumigatus sensu lato isolates in Spain. TR34 -L98H is the dominant cyp51A gene substitutions, although its presence is not widespread.